Acupuncture reduces relapse to cocaine‐seeking behavior via activation of GABA neurons in the ventral tegmental area. (7th March 2017) - Jin, Wyju; Kim, Min Sun; Jang, Eun Young; Lee, Jun Yeon; Lee, Jin Gyeom; Kim, Hong Yu; Yoon, Seong Shoon; Lee, Bong Hyo; Chang, Suchan; Kim, Jae Hyo; Choi, Kwang H.; Koo, Ho; et al.
Abstract: There is growing public interest in alternative approaches to addiction treatment and scientific interest in elucidating the neurobiological underpinnings of acupuncture. Our previous studies showed that acupuncture at a specific Shenmen (HT7) points reduced dopamine (DA) release in the nucleus accumbens (NAc) induced by drugs of abuse. The present study was carried out to evaluate the effects of HT7 acupuncture on γ‐aminobutyric acid (GABA) neuronal activity in the ventral tegmental area (VTA) and the reinstatement of cocaine‐seeking behavior. Using microdialysis and in vivo single‐unit electrophysiology, we evaluated the effects of HT7 acupuncture on VTA GABA and NAc DA release and VTA GABA neuronal activity in rats. Using a within‐session reinstatement paradigm in rats self‐administering cocaine, we evaluated the effects of HT7 stimulation on cocaine‐primed reinstatement. Acupuncture at HT7 significantly reduced cocaine suppression of GABA release and GABA neuron firing rates in the VTA. HT7 acupuncture attenuated cocaine‐primed reinstatement, which was blocked by VTA infusions of the selective GABAB receptor antagonist 2‐hydroxysaclofen. HT7 stimulation significantly decreased acute cocaine‐induced DA release in the NAc, which was also blocked by 2‐hydroxysaclofen. HT7 acupuncture also attenuated cocaine‐induced sensitization of extracellular DA levels in the NAc. Moreover, HT7 acupuncture reduced both locomotor activity and neuronal activation in the NAc induced by acute cocaine in a needle‐penetration depth‐dependent fashion. These results suggest that acupuncture may suppress cocaine‐induced DA release in the NAc and cocaine‐seeking behavior through activation of VTA GABA neurons. Acupuncture may be an effective therapy to reduce cocaine relapse by enhancing GABAergic inhibition in the VTA. Abstract : We provide Figure4 b as a suitable figure. We also summarized 3 sentences from our findings. HT7 acupuncture significantly reduced cocaine suppression of γ‐aminobutyric acid (GABA) release and GABA neuron firing rates in the ventral tegmental area. HT7 acupuncture attenuated cocaine‐primed reinstatement and cocaine‐induced sensitization of extracellular dopamine levels in the nucleus accumbens, which are blocked by GABAB receptor antagonist 2‐hydroxysaclofen. HT7 acupuncture reduced both locomotor activity and neuronal activation in the nucleus accumbens induced by acute cocaine in a needle‐penetration depth‐dependent fashion.